IoT-Based Personal Protective Equipment Monitoring System to Prevent the Risk of Dehydration in Health Workers for COVID-19 Pandemic - Fadilla, Rafa (Publisher Cv. Inara, 2021)
The extraordinary case of Covid-19 has made health workers the front line in handling it. To prevent the risk of contracting, health workers must use Personal Protective Equipment (PPE) as protection. PPE that must be worn for at least 5 hours a day and is waterproof makes users experience much sweating. If not prevented, health workers can be exposed to dehydration and even death. Based on the explanation above, PPE has been designed that can cool IoT-based health workers. Also, all activities can be monitored remotely via the WEB, accessible via a smartphone or computer. In addition to WEB, data can be displayed via the LCD. The DHT22 sensor and the airflow sensor will detect the hazmat's temperature, humidity, and airflow. Furthermore, the tool is also equipped with UVC rays that can clean the air from microorganisms. Activity data will be stored in cloud storage, which is helpful as an evaluation material and reference for health workers' health progress. From the tests' results, the tool will function when the temperature and humidity follow the setpoint.